The link between conduct disorder and adult antisocial behaviour is partially mediated by early onset alcohol abuse - Khalifa, Najat Rasool (2012)
This study sought to clarify the nature of the relationship between conduct disorder (CD), early-onset alcohol abuse (EOAA), some other externalizing-related constructs and adult violent antisociality (VA). It addressed two key questions: (i) whether EOAA mediated the link between CD and VA; and (ii) whether the effects of EOAA on VA were, in turn, mediated by impulsiveness, ventro-medial prefrontal cortex (vm-PFC) dysfunction and social deviance as measured by the Psychopathy Checklist-Revised (PCL-R). It tested the hypothesis that in the context of early disinhibitory psychopathology, e.g. CD, EOAA disrupts the neural substrates of self-regulation in vm-PFC during a critical neurodevelopmental period (i.e. before age 20). Consequently, on entry into adulthood the vm-PFC is functionally impaired and personality suffers maladaptive development which would then take the form of increased impulsiveness and social deviance, placing the individual at high risk of violent antisocial behaviour.